Investigation of Antioxidant, Antimicrobial and Cytotoxic Activity of Cydonia oblonga Leaf on Breast Cancer (MCF-7) and Liver Cancer (HepG2) Cell Lines - Dalkilic, Lütfiye Kadioglu (My University, 2024)
Cancer, one of the most common pathologies in the world, has been reducing the standard of living of many people for centuries and can cause death. Many medicinal plants are widely used in cancer treatment due to their ability to improve disease symptoms and low side effects. Cydonia oblonga (C. oblonga) leaf, which is among the medicinal plants and has important health properties, is a type of plant commonly known as quince leaf. Although it originates from Asia, it is cultivated in many countries today. In this study, antioxidant, antimicrobial and cytotoxic activities of C. oblonga leaves on MCF-7 and HepG2 cell lines were investigated. As a method, the collected C. oblonga leaves were extracted in methanol and hexane solvents. The extracts were tested on MCF-7 and HepG2 cell lines using MTT Assay method for cytotoxic activity, DPPH method for antioxidant activity and well agar method for antimicrobial effects of the extract on five different microorganisms. As a results, although C. oblonga leaf in both cell lines hexane extract exhibited stronger cytotoxic activity than methanol extract, methanol extract was found to have stronger antioxidant effect than hexane extract. The extracts applied to microorganisms showed the best zone diameter effect on E. coli and the lowest effect on B. megaterium. In addition, it was observed that C. oblonga leaf has stronger antimicrobial effects than anticancer and antioxidant activity.
Keywords: Antioksidan aktivite; antimikrobiyal aktivite; Cydonia oblonga; sitotoksik aktivite